"Playing with the Border:" Alsatian Sports Societies and Alsace's Problematic Return to France after the First World War. Issue 3 (26th May 2020) - Jallat, Denis; Stumpp, Sébastien; Fuchs, Julien
ABSTRACT: Annexed by the Germans in 1870, the Alsace region returned to France in 1918. Following a triumphal welcome for French troops, the Alsatians began timidly to showcase their new nationality after 47 years of German presence. In a country that promoted anti-Germanism, laying claim to German heritage on the political or professional scene was impossible. The situation was quite different however in the field of sport, which cultivated contradictions by playing on its neutral and apolitical image. Local sports associations maintained a special relationship with the border, characterized by porosity with regard to Germany and the partitioning of the French or even Alsatian side. Such ambiguous positioning led them to hesitate between two different approaches: either adopt a public position proclaiming their commitment to the Republic or take an infrapolitical stand and "play with the new borders." The paper studies this phenomenon through the monograph of the rowing club "Cercle Nautique de Strasbourg."